Perioperative fasting time among cancer patients submitted to gastrointestinal surgeries - Nayara de Castro Pereira; Ruth Natalia Teresa Turrini; Vanessa de Brito Poveda
Abstract OBJECTIVE To identify the length of perioperative fasting among patients submitted to gastrointestinal cancer surgeries. METHOD Retrospective cohort study, developed by consulting the medical records of 128 patients submitted to gastrointestinal cancer surgeries. RESULTS The mean of total length of fasting was 107.6 hours. The total length of fasting was significantly associated with the number of symptoms presented before (p=0.000) and after the surgery (p=0.007), the length of hospital stay (p=0.000), blood transfusion (p=0.013), nasogastric tube (p=0.001) and nasojejunal tube (p=0,003), postoperative admission at ICU (p=0.002), postoperative death (p=0.000) and length of preoperative fasting (p=0.000). CONCLUSION The length of fasting is associated with complications that affect the quality of the patients' postoperative recovery and nurses' work. The nursing team should be alert to this aspect and being responsible for overseeing the patients' interest, should not permit the unnecessary extension of fasting.